Analisis Aliran Daya Terhadap Pengaruh Masuknya Gardu Induk Bombana Pada Sistem Sultra Menggunakan Software ETAP (Electrical Transient Electrical Program) - Malikurrahim; Tachrir; Sahabuddin Hay; Mustarum Musaruddin; Yuni Koedoes; Agustinus Lolok; Gamal Abdel Nasser Masikki (Program Pendidikan Vokasi Teknik Mesin, 2024)
The current Southeast Sulawesi electricity system has two main power plants, namely the Nii Tanasa PLTU with a capacity of (1´30 MW) and the Moramo PLTU (DSSP) with a capacity of (2´50) MW and has also been interconnected with the South Sulawesi electricity system with the addition of a substation in Bombana, meaning that the power needs of the Kendari electricity system have increased, which can result in increased losses and drop voltage . The purpose of this study is to see the condition of the large value of Current, Voltage, active power flow and reactive power on each bus between channels, and to see the value of the short circuit fault current at the fault location point. after the addition of the Bombana GI, Single line modeling using the help of ETAP 19.0.1 software. based on the results of the research that has been done the value of the power generated by the generator after the entry of the Bombana GI is 271.527 MW where previously it was 211.975 MW, the voltage condition before the entry of the Bombana GI is 96.05% - 99.23% of the previous 97.95% - 99.53%, based on the percentage of Drop Voltage is in the range of 0.022%−0.872% which is still within the SPLN operational standard limit. Then the Total Losses on the channel is 1168.92 KW. The largest Short Circuit current value after the entry of the Bombana GI in the Southeast Sulawesi system for 3-phase short circuit current is 10.267 KA, phase to ground is 10.637 KA, phase to phase is 8.920 KA, and two phases to ground is 10.537 KA.